2018
DOI: 10.1016/j.omtm.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Recombinant Adeno-Associated Virus Production System Using Human Bocavirus 1 Helper Genes

Abstract: Human bocavirus 1 (HBoV1), an autonomous parvovirus, is a helper virus supporting replication of wild-type adeno-associated virus 2 (AAV2). In this study, we compared the helper functions from HBoV1 with those from adenovirus (Ad) for the production of recombinant AAV (rAAV) vector in HEK293 cells. We demonstrated that triple plasmids transfection of (1) a cloned HBoV1 helper minigenome (pBocaHelper) that expresses HBoV1 genes NP1, NS2, and BocaSR, (2) pAAV transfer plasmid, and (3) pAAVRepCap supports rAAV pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…This interesting observation led to a couple of assumptions on the molecular functions of NS2 and NS4; however, the detailed molecular mechanism of how HBoV1 supports AAV replication is not known. The same research group then utilized this bocavirus helper system in order to develop a novel rAAV vector production platform that may have implications in future AAV gene therapy vector production [ 226 ]. They combined a distinct set of AdV and bocavirus helper genes and found that rAAV titers were significantly increased when compared to rAAV vector titers that have been produced with either AdV or bocavirus helper factors alone.…”
Section: Helper Viruses and Aavmentioning
confidence: 99%
“…This interesting observation led to a couple of assumptions on the molecular functions of NS2 and NS4; however, the detailed molecular mechanism of how HBoV1 supports AAV replication is not known. The same research group then utilized this bocavirus helper system in order to develop a novel rAAV vector production platform that may have implications in future AAV gene therapy vector production [ 226 ]. They combined a distinct set of AdV and bocavirus helper genes and found that rAAV titers were significantly increased when compared to rAAV vector titers that have been produced with either AdV or bocavirus helper factors alone.…”
Section: Helper Viruses and Aavmentioning
confidence: 99%
“…Deng et al reported that, with the co-infection of a BEV expressing HBoV1 NP1, the rAAV2/HBoV1 vector was produced in a higher quantity and with a lower percentage of empty particles [ 26 ]. The expression of NP1 led to an increase in rAAV2 replicative-form (RF) DNA intermediates, which may be responsible for the enhanced production [ 11 ]. Another vital reason may be that the ratio of the AAV2 genome and the capsid gene of HBoV1 was not optimal.…”
Section: Discussionmentioning
confidence: 99%
“…Human bocavirus type-1 (HBoV1) has a high tropism for the apical membrane of human airway epithelia [ 10 ]. The packaging of a rAAV serotype 2 genome into a HBoV1 capsid produces a chimeric vector (rAAV2/HBoV1) that also efficiently transduces human airway epithelia [ 11 ]. This chimeric vector has shown potential for use in gene therapies for cystic fibrosis (CF) and other lung diseases [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, OVs can express toxic proteins, induce inflammatory cytokines such as TNF, and trigger the immune response [ 26 ]. Gene therapy using conditional replicated AAV has become an important focus of tumor gene therapy [ 27 ]. There are 2 main approaches to constructing targeted rAAV.…”
Section: Discussionmentioning
confidence: 99%